2011
DOI: 10.1182/blood-2010-11-316463
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and intracellular compartmentalization of HTLV-1 gene expression: nuclear retention of HBZ mRNAs

Abstract: IntroductionHuman T-cell leukemia virus type 1 (HTLV-1) is the causative agent of adult T-cell leukemia-lymphoma (ATLL) and tropical spastic paraparesis/HTLV-1-associated myelopathy (TSP/HAM). HTLV-1 uses several strategies for controlling the expression of its genome, including the production of 9 alternatively spliced transcripts ( Figure 1A). 1-6 Production of plus-strand transcripts is controlled by Tax at the level of transcription and by Rex at the level of nucleo-cytoplasmic export of unspliced and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
152
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(167 citation statements)
references
References 20 publications
(13 reference statements)
15
152
0
Order By: Relevance
“…This would be consistent with the persistent expression of HBZ in HTLV-1-infected cells (2,25). In addition, insufficient HBZ-specific T cell responses may be due, in part, to the fact that the majority of the HBZ mRNA is retained in the nucleus, which may inhibit its translation (35), and probably leads to a low level of HBZ protein expression in HTLV-1-infected cells (29). In contrast, the finding that HLA-DRB1*15:01-restricted or HLA-DRB1*15:02-restricted HBZ-specific CD4 T cell responses were detected in ATL patients after allogeneic HCT requires explanation.…”
Section: Discussionsupporting
confidence: 55%
“…This would be consistent with the persistent expression of HBZ in HTLV-1-infected cells (2,25). In addition, insufficient HBZ-specific T cell responses may be due, in part, to the fact that the majority of the HBZ mRNA is retained in the nucleus, which may inhibit its translation (35), and probably leads to a low level of HBZ protein expression in HTLV-1-infected cells (29). In contrast, the finding that HLA-DRB1*15:01-restricted or HLA-DRB1*15:02-restricted HBZ-specific CD4 T cell responses were detected in ATL patients after allogeneic HCT requires explanation.…”
Section: Discussionsupporting
confidence: 55%
“…The function of the RNA has not been characterized fully, but a report suggested that HBZ mRNA is localized mostly in the nucleus [20]. This nuclear localization may suggest other roles of HBZ mRNA in addition to its translation in the cytoplasm.…”
Section: Function Of Hbz Rnamentioning
confidence: 99%
“…After co-incubation with either HBZ-specific or Tax-specific CTLs, there was a significant reduction in the median intensity of HLA-A*02 expression by Tax + CD4 + cells ( Figure 6C). In contrast, the level of HLA-A*02 expression was unchanged on Tax We hypothesized that Tax [11][12][13][14][15][16][17][18][19] could inhibit presentation of HBZ [26][27][28][29][30][31][32][33][34] by competing for binding to HLA-A*0201 ( Figure 7A). At saturating concentrations of HBZ 26-34 (2 uM), preincubation with Tax 11-19 had no effect on lysis of BLCL by CTLs.…”
Section: Cd4mentioning
confidence: 99%
“…However, when the concentration of HBZ [26][27][28][29][30][31][32][33][34] was limiting (0.02-0.2 uM), Tax [11][12][13][14][15][16][17][18][19] could inhibit CTL detection of HBZ, but only when present in 10,000-fold molar excess. We also quantified the frequency of CD8 + T cells specific for the Tax [11][12][13][14][15][16][17][18][19] and HBZ [26][27][28][29][30][31][32][33][34] epitopes in each of the donors in this study. IFN-γ-producing Tax [11][12][13][14][15][16][17][18][19] specific CD8 + cells were observed in all individuals, whereas no HBZ 26-34 specific CD8 + cells were detected ( Figure 7B).…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation